A comparative study of cinnamomum cassia (CINNAMON) bark oil extraction through hydrodistillation (HD) and microwave assisted hydrodistillation (MAHD) - Nitthiyah, Jeyaratnam (2016)
The use of natural origin essential oils has recently gained much attention in many fields such as food flavouring, pesticides and in pharmaceutical industries. However, limitations to the use of existing conventional extraction methods are the inherent time consumption, high cost, high power consumption, potential loss of volatile compounds from essential oils as well as environmental concerns. Therefore new innovative extraction techniques are required to overcome these limitations. In this research, essential oil was extracted from Cinnamomum cassia bark using conventional hydrodistialltion (HD) and non-conventional microwave assisted hydrodistillation (MAHD) methods. The influence of pre-treatment on the C. cassia bark prior to extraction was investigated. Also, changes in morphology of the cinnamon bark powder before and after extraction by the two methods was observed through SEM. Milder disruption of cinnamon bark oil gland was observed for MAHD compared to HD. This is associated with the effective heat distribution obtainable from MAHD. The efficiency of MAHD extraction technique was compared with HD in terms of chemical composition and biological activity of the oil obtained as well as cost implication of the extraction process. To justify the performance of MAHD technique, the three main influencing factors such as solvent-to-plant material ratio, extraction time and irradiation microwave power were analysed. Analysis of these factors was initially carried out using one factor at a time (OFAT) method. Furthermore, screening and optimization of the factors was conducted with the help of Design expert software via factorial analysis and central composite design (CCD) respectively. The optimum conditions obtained through CCD for MAHD is 75 min extraction time, 8:1 of water to raw material ratio and 225 W irradiation power. The maximum yield obtained is 2.75 %. On the other hand, the extraction parameters for HD are 150 min extraction time, 8:1 of water to raw material ratio and a constant operating power of 350 W. The maximum yield obtained for HD is 2.02 %. The essential oil obtained at the optimum operating conditions for both methods was subjected to further qualitative analysis. Compositional analysis was conducted through gas chromatography-mass spectrometry (GC-MS). A total of 36 compounds were found for both extraction methods which were supported by FTIR analysis. However, the active compound present in C. cassia bark oil (trans-cinnamaldehyde) manifested a mean value of 84.43 ± 0.70 and 79.55 ± 0.45 for MAHD and HD respectively. Furthermore, cassia crude extract obtained through MAHD exhibits larger proportion of oxygenated compounds (9 % higher) than HD method. Energy consumption analysis shows that MAHD is more energy saving and environmental friendly. It reduced the overall carbon dioxide emission from HD by 59 %. In addition, cytotoxicity studies revealed that essential oil obtained through MAHD showed lower LC50 value (51.21 ppm) than HD (68.88 ppm). This indicates that the MAHD technique is suitable for obtaining volatile oils from cinnamon cassia bark and the oil obtained can offer great pharmaceutical benefits.